Plasma meltallizing metal coating and preparation method thereof

The zinc-aluminum alloy powder core wire material and modified organic coating are sprayed through plasma melting technology to form a corrosion-resistant metal coating, which solves the problem that the prior art is difficult to protect the metal structure under extreme operating conditions, and achieves a longer service life and lower maintenance costs.

CN119842252AInactive Publication Date: 2025-04-18JINAN DINGHUA WEAR RESISTANT MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510128369.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively protect metal structures from corrosion under extreme operating conditions, resulting in a shorter service life of mechanical parts and an increased maintenance cost.

Method used

The zinc-aluminum alloy powder core wire is sprayed on the surface of the substrate by plasma melting technology, and then scraped with modified organic coatings and cured ultraviolet light to form a corrosion-resistant metal coating.

Benefits of technology

It improves the corrosion resistance and mechanical strength of metal coatings, extends the service life of mechanical parts, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005260654540000031
    Figure BDA0005260654540000031
  • Figure BDA0005260654540000032
    Figure BDA0005260654540000032
  • Figure BDA0005260654540000041
    Figure BDA0005260654540000041
Patent Text Reader

Abstract

The invention discloses a plasma meltallizing metal coating and a preparation method thereof, and relates to the technical field of metal coatings. When the plasma meltallizing metal coating is prepared, firstly, zinc, aluminum, titanium, cerium oxide and silicon carbide ceramic are mixed, and then the mixture and a zinc-aluminum alloy strip are prepared into a meltallizing alloy powder core wire; monoethyl phosphate and hydroxyethyl methylacrylate are subjected to a reaction, and olefin modified phosphate is prepared; the preparation method comprises the following steps: reacting isophorone diisocyanate, ethylene glycol dimercaptoacetate, polycarbonate diol and olefin modified phosphate to prepare modified polythionocarbamate; mixing the modified polythionocarbamate with a diluent, a photoinitiator and a catalyst, and defoaming to obtain a modified organic coating; the method comprises the following steps: spraying a meltallizing alloy powder core wire on the surface of a substrate by using a plasma meltallizing method, blade-coating the modified organic coating by using a blade-coating method, and carrying out ultraviolet light curing to obtain the plasma meltallizing metal coating. The prepared plasma spray metal coating has the advantages of being high in impact strength, high in bonding strength and good in corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal coatings, in particular to a plasma spraying metal coating and a preparation method thereof. Background Art

[0002] As an important raw material for infrastructure construction, metal is still in great demand, involving various industries such as non-ferrous metals, energy, electricity, machinery, papermaking, bridges, ships, and automobiles. With the continuous development of science and technology in today's society, more and more complex production conditions have put forward more stringent technical requirements for mechanical equipment. In order to make mechanical parts meet the use requirements of extreme working conditions, the traditional practice of replacing parts obviously has great technical difficulties and high costs. Corrosion is an inevitable problem, and most of the failure processes of metal materials are caused by corrosion failure. Corrosion is one of the important forms of metal failure, especially in marine environments, where chloride ions in seawater or the atmosphere are adsorbed on the metal surface, causing local damage to the metal. Therefore, it is of great significance to prepare a corrosion-resistant coating on the surface of the metal structure by plasma spraying to increase the service life of the structural parts and reduce the cost of later maintenance.

[0003] Plasma spraying technology can make it have better performance and wider application range without changing the original materials. The heat source of plasma spraying technology has a wide temperature range and can melt most solid materials, such as metals, ceramics and organic plastics. Plasma spraying can not only prepare special functional coatings such as wear resistance, corrosion resistance, high temperature resistance and oxidation resistance, but also the substrate heating area is small during the spraying process, and the heat source can be freely moved according to actual needs, so the operation is very flexible. The principle of plasma spraying technology is to use a heat source to heat the powdered or filamentary spraying material to a molten or semi-molten state, and spray it onto the surface of the substrate at a high speed to form a coating. The coating prepared by plasma spraying can effectively protect the working surface of parts, extend their service life and improve safety. Therefore, it is widely used in metallurgical industry, medical equipment, automobile transportation and other industries, generating very significant economic benefits. At the same time, the use of plasma spraying technology to repair and remanufacture damaged parts of mechanical parts can reduce resource waste and achieve sustainable industrial development. Summary of the invention

[0004] The object of the present invention is to provide a plasma spraying metal coating and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A plasma spraying metal coating, wherein the plasma spraying metal coating is prepared by first spraying a spraying alloy powder core wire on a substrate surface by a plasma spraying method, then scraping a modified organic coating thereon by a scraping method, and then curing the coating with ultraviolet light;

[0007] The spray-coated alloy powder core wire is prepared by mixing zinc powder, aluminum powder, titanium powder, cerium oxide powder and silicon carbide ceramic powder with a zinc-aluminum alloy strip through a powder core wire preparation process, wherein the components by mass fraction are 38% to 45% zinc, 7% to 9% aluminum, 5% to 6% titanium, ≤0.5% cerium and 40% to 50% silicon carbide;

[0008] The modified organic coating is prepared by mixing modified polythiourethane with a diluent, a photoinitiator and a catalyst for defoaming;

[0009] The modified polythiourethane is prepared by reacting isophorone diisocyanate, ethylene glycol dimercaptoacetate, and olefin-modified phosphate;

[0010] The olefin-modified phosphate is prepared by reacting monoethyl phosphate with hydroxyethyl methacrylate.

[0011] As an optimization, the zinc-aluminum alloy strip is made of zinc-aluminum alloy, the aluminum content in the zinc-aluminum alloy is 2wt%, the impurity content is less than 0.01wt%, and the balance is zinc.

[0012] As an optimization, the diluent is one of dipropylene glycol diacrylate and tripropylene glycol diacrylate.

[0013] As optimization, the photoinitiator is one or more of Irgacure 127, Irgacure 184, Irgacure 369, Irgacure 907, and Irgacure 1173.

[0014] As an optimization, the catalyst is 1,5-diazabicyclo[4.3.0]non-5-ene.

[0015] As an optimization, the model of the polycarbonate diol is P997425, and the weight average molecular weight is 500.

[0016] A method for preparing a plasma sprayed metal coating comprises the following steps:

[0017] (1) The zinc-aluminum alloy is made into a zinc-aluminum alloy strip, and then zinc powder, aluminum powder, titanium powder, cerium oxide powder, and silicon carbide ceramic powder are mixed according to the mass fraction composition of zinc 38% to 45%, aluminum 7% to 9%, titanium 5% to 6%, cerium ≤ 0.5%, and silicon carbide 40% to 50%, and the mixture is mixed with the zinc-aluminum alloy strip to form a melt-sprayed alloy powder core wire with a diameter of 2.0 mm;

[0018] (2) at 40-45° C., monoethyl phosphate and hydroxyethyl methacrylate were uniformly mixed in a molar ratio of 1:1, and then stirred in a closed environment at 80-85° C. and 200-300 r / min for 4-5 hours, and then cooled and purified to obtain olefin-modified phosphate;

[0019] (3) According to the mass fraction, 11.11-13.34 parts of isophorone diisocyanate, 0.0022-0.0027 parts of triethylamine and 20-25 parts of ethyl acetate were mixed uniformly under nitrogen atmosphere, and 5.26-7.99 parts of ethylene glycol dimercaptoacetate were added dropwise at 25-30°C and 200-300 r / min at a rate of 2-3 drops per second. After the addition was completed, the mixture was reacted at 25-30°C and 200-300 r / min for 2-3 hours. After sampling to confirm that the reaction was complete, 5-6 parts of polycarbonate were added dropwise at a rate of 2-3 drops per second. Acid ester diol, 0.005-0.006 parts of dibutyltin dilaurate, after the addition is completed, react at 65-70°C, 200-300r / min for 3-4h, take samples to confirm that the reaction is complete, then add 4.76-7.15 parts of olefin modified phosphate ester and 0.01-0.012 parts of p-hydroxyanisole at a rate of 2-3 drops per second, after the addition is completed, react at 65-70°C, 200-300r / min for 3-4h, take samples to confirm that the reaction is complete, stop the reaction, remove ethyl acetate by rotary evaporation, and obtain modified polythiourethane;

[0020] (4) Mixing 70 to 80 parts by mass of modified polythiourethane, 25 to 35 parts of diluent, 2 to 3 parts of photoinitiator, and 0.05 to 0.06 parts of catalyst in a mixing and defoaming machine to obtain a modified organic coating;

[0021] (5) After setting the equipment according to the plasma spraying process parameters, the sprayed alloy powder core wire is sprayed on the surface of the substrate with a spraying thickness of 150-160 μm, and then the modified organic coating is scraped on with a scraping thickness of 40-50 μm. The UV light curing machine is used for light curing, and the exposure curing energy is 800-850 mJ / cm 2 , to obtain a plasma sprayed metal coating.

[0022] As an optimization, the particle sizes of the zinc powder, aluminum powder, titanium powder, cerium oxide powder and silicon carbide ceramic powder in step (1) are all 325 meshes.

[0023] As an optimization, the reaction process of the olefin-modified phosphate in step (2) is as follows:

[0024]

[0025] As an optimization, the reaction process of the modified polythiourethane in step (3) is as follows:

[0026]

[0027]

[0028] As an optimization, the plasma spraying process parameters of step (5) are voltage 130-135V, current 400-420A, argon flow rate 140-150L / min, hydrogen flow rate 10-12L / min, and spraying distance 110-120mm.

[0029] As an optimization, the substrate in step (5) can be made of any metal material, and the substrate is pre-treated by grinding, cleaning and then sandblasting the substrate.

[0030] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0031] When preparing the plasma spraying metal coating, the present invention first prepares the zinc-aluminum alloy into the zinc-aluminum alloy strip, mixes the zinc powder, aluminum powder, titanium powder, cerium oxide powder and silicon carbide ceramic powder with the zinc-aluminum alloy strip to prepare the spraying alloy powder core wire; reacts monoethyl phosphate with hydroxyethyl methacrylate to prepare olefin modified phosphate; reacts isophorone diisocyanate, ethylene glycol dimercaptoacetate, polycarbonate diol and olefin modified phosphate to prepare modified polythiourethane; mixes the modified polythiourethane with a diluent, a photoinitiator and a catalyst to defoam and prepare a modified organic coating; sprays the spraying alloy powder core wire on the surface of the substrate by a plasma spraying method, and then scrapes the modified organic coating by a scraping method, and then cures the plasma spraying metal coating by ultraviolet light.

[0032] First, the zinc-aluminum alloy is made into a zinc-aluminum alloy strip, and zinc powder, aluminum powder, titanium powder, cerium oxide powder, and silicon carbide ceramic powder are mixed with the zinc-aluminum alloy strip to make a sprayed alloy powder core wire. The zinc-aluminum alloy strip is no longer as soft and easy to deform as pure zinc because of the addition of aluminum. The zinc-aluminum alloy has higher hardness and rigidity. As the outer skin material of the powder core wire, it has good ductility and rigidity and better reliability. At the same time, the alloy layer formed by zinc, aluminum, titanium, and cerium has excellent corrosion resistance. At the same time, the corrosion intermediate product formed has density, which can self-seal the corrosion cracks after corrosion occurs to prevent further corrosion. The added silicon carbide ceramic powder is used as a hard phase, and its higher melting point makes it incompletely melted during the plasma spraying process. Through physical action, the alloy coating has higher density, reduces the generation of pores and microcracks, and improves corrosion resistance and mechanical strength.

[0033] Secondly, olefin-modified phosphate is prepared by reacting monoethyl phosphate with hydroxyethyl methacrylate; isophorone diisocyanate, ethylene glycol dimercaptoacetate, polycarbonate diol and olefin-modified phosphate are reacted to prepare modified polythiourethane; the modified polythiourethane is mixed with a diluent, a photoinitiator and a catalyst for defoaming to prepare a modified organic coating. Olefin-modified phosphate contains both phosphate groups and olefins. After being connected to the main chain of polythiourethane as a capping agent, a subsequent cross-linking reaction can be carried out. A cross-linking network is formed under the action of a photoinitiator to cure. At the same time, the phosphate group has good metal chelating properties, which can form a phosphating film at the metal-organic interface. While improving the bonding strength between the organic coating and the metal, it can also be used as a A line of defense to prevent the penetration of corrosive media improves the corrosion resistance. The main chain segment of polythiourethane is not like traditional polyurethane, which uses hydroxyl and amino groups as chain extenders. It is formed by the reaction of thiol groups and isocyanate groups. The thiolcarbamate bonds formed have the ability of dynamic exchange. During the photocuring process, the shrinkage stress generated can be effectively dissipated to improve the mechanical properties and bonding strength of the coating after curing. The dithioglycolate used as a thiol chain extender contains a large amount of sulfur and oxygen elements, has excellent metal chelating ability, and can effectively improve the bonding strength. At the same time, the dynamic exchange ability of the thiolcarbamate bond has the ability of self-repairing, which can fully fill the microcracks of the alloy coating and further improve the corrosion resistance.

[0034] Finally, the plasma spraying method is used to spray the alloy powder core wire onto the surface of the substrate, and then the modified organic coating is scraped on by the scraping method. After ultraviolet light curing, the plasma sprayed metal coating is obtained. The alloy coating formed by the sprayed alloy powder core wire has a self-sealing effect, which can effectively seal the microcracks of the organic coating upward, and the dynamic exchange ability of the thiocarbamate bonds in the organic coating also gives it self-repairing ability, which can repair some smaller cracks. At the same time, the phosphate group also has good metal chelating ability, combined with the complexing ability of nitrogen, sulfur, and oxygen elements, it can adsorb metal ions when corrosion occurs and expand the volume to seal the cracks. The organic coating and the alloy coating protect each other, and the composed plasma sprayed metal coating has good corrosion resistance and bonding strength. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The raw materials used in all the following examples and comparative examples are as follows:

[0037] Diluent: dipropylene glycol diacrylate;

[0038] Photoinitiator: Irgacure 1173;

[0039] Catalyst: 1,5-diazabicyclo[4.3.0]non-5-ene.

[0040] The substrates used in all the following embodiments and comparative examples are 304 steel sheets that have been pretreated. The pretreatment method is to clean them with acetone after polishing, and to sandblast them with a sandblasting machine after drying. The surface cleanliness reaches the Sa3 level in GB / T8923.1-2011.

[0041] Embodiment 1:

[0042] A method for preparing a plasma sprayed metal coating, the method comprising the following steps:

[0043] (1) The zinc-aluminum alloy is made into a zinc-aluminum alloy strip, and then zinc powder, aluminum powder, titanium powder, cerium oxide powder, and silicon carbide ceramic powder are mixed according to the mass fraction composition of zinc 38%, aluminum 7%, titanium 5%, cerium ≤ 0.5%, and silicon carbide 49.5%, and the mixture is mixed with the zinc-aluminum alloy strip to form a melt-sprayed alloy powder core wire with a diameter of 2.0 mm;

[0044] (2) at 40° C., monoethyl phosphate and hydroxyethyl methacrylate were mixed uniformly in a molar ratio of 1:1, and then stirred in a closed environment at 80° C. and 200 r / min for 5 h, and then cooled and purified to obtain olefin-modified phosphate;

[0045] (3) According to the mass fraction, 11.11 parts of isophorone diisocyanate, 0.0022 parts of triethylamine and 20 parts of ethyl acetate were mixed uniformly under a nitrogen atmosphere, and 5.26 parts of ethylene glycol dithioacetate were added dropwise at 2 drops per second at 25°C and 200 r / min. After the addition was completed, the mixture was reacted at 25°C and 200 r / min for 3 hours. After sampling to confirm that the reaction was complete, 5 parts of polycarbonate diol and 0.005 parts of dibutyltin dilaurate were added dropwise at 2 drops per second. After the addition was completed, the mixture was reacted at 65°C and 200 r / min for 4 hours. After sampling to confirm that the reaction was complete, 7.15 parts of olefin-modified phosphate and 0.012 parts of p-hydroxyanisole were added dropwise at 2 drops per second. After the addition was completed, the mixture was reacted at 65°C and 200 r / min for 4 hours. After sampling to confirm that the reaction was complete, the reaction was stopped, and the ethyl acetate was removed by rotary evaporation to obtain a modified polythiourethane;

[0046] (4) Mix 70 parts of modified polythiourethane, 25 parts of diluent, 2 parts of photoinitiator, and 0.05 parts of catalyst in a mixing and defoaming machine to obtain a modified organic coating;

[0047] (5) After setting up the equipment according to the plasma spraying process parameters of voltage 130V, current 420A, argon flow rate 140L / min, hydrogen flow rate 10L / min, and spraying distance 110mm, the sprayed alloy powder core wire is sprayed on the surface of the substrate with a spraying thickness of 150μm, and then the modified organic coating is scraped on with a scraping thickness of 50μm. The UV light curing machine is used for light curing, and the exposure curing energy is 800mJ / cm 2 , to obtain a plasma sprayed metal coating.

[0048] Embodiment 2:

[0049] A method for preparing a plasma sprayed metal coating, the method comprising the following steps:

[0050] (1) The zinc-aluminum alloy is made into a zinc-aluminum alloy strip, and then zinc powder, aluminum powder, titanium powder, cerium oxide powder, and silicon carbide ceramic powder are mixed according to the mass fraction composition of zinc 42%, aluminum 8%, titanium 5.5%, cerium ≤ 0.5%, and silicon carbide 44%, and the mixture is mixed with the zinc-aluminum alloy strip to form a melt-sprayed alloy powder core wire with a diameter of 2.0 mm;

[0051] (2) at 42° C., monoethyl phosphate and hydroxyethyl methacrylate were mixed uniformly in a molar ratio of 1:1, and then stirred in a closed environment at 82° C. and 250 r / min for 4.5 h, and then cooled and purified to obtain olefin-modified phosphate;

[0052] (3) According to the mass fraction, 12.23 parts of isophorone diisocyanate, 0.0024 parts of triethylamine and 22.5 parts of ethyl acetate were mixed uniformly under a nitrogen atmosphere, and 6.73 parts of ethylene glycol dithioacetate were added dropwise at 28°C and 250r / min at a rate of 3 drops per second. After the addition was completed, the mixture was reacted at 28°C and 250r / min for 2.5h. After sampling to confirm that the reaction was complete, 5.5 parts of polycarbonate diol and 0.0055 parts of dibutyltin dilaurate were added dropwise at a rate of 3 drops per second. After the addition was completed, the mixture was reacted at 68°C and 250r / min for 3.5h. After sampling to confirm that the reaction was complete, 5.72 parts of olefin-modified phosphate and 0.011 parts of p-hydroxyanisole were added dropwise at a rate of 3 drops per second. After the addition was completed, the mixture was reacted at 68°C and 250r / min for 3.5h. After sampling to confirm that the reaction was complete, the reaction was stopped, and the ethyl acetate was removed by rotary evaporation to obtain a modified polythiourethane;

[0053] (4) Mix 75 parts of modified polythiourethane, 30 parts of diluent, 2.5 parts of photoinitiator, and 0.055 parts of catalyst in a mixing and defoaming machine to obtain a modified organic coating;

[0054] (5) After setting up the equipment according to the plasma spraying process parameters of voltage 132V, current 410A, argon flow rate 145L / min, hydrogen flow rate 11L / min, and spraying distance 115mm, the sprayed alloy powder core wire is sprayed on the surface of the substrate with a spraying thickness of 155μm, and then the modified organic coating is scraped on with a scraping thickness of 45μm. The UV light curing machine is used for light curing, and the exposure curing energy is 825mJ / cm 2 , to obtain a plasma sprayed metal coating.

[0055] Embodiment 3:

[0056] A method for preparing a plasma sprayed metal coating, the method comprising the following steps:

[0057] (1) The zinc-aluminum alloy is made into a zinc-aluminum alloy strip, and then zinc powder, aluminum powder, titanium powder, cerium oxide powder, and silicon carbide ceramic powder are mixed according to the mass fraction composition of zinc 44.5%, aluminum 9%, titanium 6%, cerium ≤ 0.5%, and silicon carbide 40%, and the mixture is mixed with the zinc-aluminum alloy strip to form a melt-sprayed alloy powder core wire with a diameter of 2.0 mm;

[0058] (2) at 45° C., monoethyl phosphate and hydroxyethyl methacrylate were mixed uniformly in a molar ratio of 1:1, and then stirred in a closed environment at 85° C. and 300 r / min for 4 h, and then cooled and purified to obtain olefin-modified phosphate;

[0059] (3) According to the mass fraction, 13.34 parts of isophorone diisocyanate, 0.0027 parts of triethylamine and 25 parts of ethyl acetate were mixed uniformly under a nitrogen atmosphere, and 7.99 parts of ethylene glycol dithioacetate were added dropwise at 30°C and 300 r / min at a rate of 3 drops per second. After the addition was completed, the mixture was reacted at 30°C and 300 r / min for 2 hours. After sampling to confirm that the reaction was complete, 6 parts of polycarbonate diol and 0.006 parts of dibutyltin dilaurate were added dropwise at a rate of 3 drops per second. After the addition was completed, the mixture was reacted at 70°C and 300 r / min for 3 hours. After sampling to confirm that the reaction was complete, 4.76 parts of olefin-modified phosphate and 0.01 parts of p-hydroxyanisole were added dropwise at a rate of 3 drops per second. After the addition was completed, the mixture was reacted at 70°C and 300 r / min for 3 hours. After sampling to confirm that the reaction was complete, the reaction was stopped, and the ethyl acetate was removed by rotary evaporation to obtain a modified polythiourethane;

[0060] (4) 80 parts by mass of modified polythiourethane, 35 parts by mass of diluent, 3 parts by mass of photoinitiator, and 0.06 parts by mass of catalyst were mixed uniformly in a mixing and defoaming machine to prepare a modified organic coating;

[0061] (5) After setting up the equipment according to the plasma spraying process parameters of voltage 135V, current 400A, argon flow rate 150L / min, hydrogen flow rate 12L / min, and spraying distance 120mm, the sprayed alloy powder core wire is sprayed on the surface of the substrate with a spraying thickness of 160μm, and then the modified organic coating is scraped on with a scraping thickness of 40μm. The UV light curing machine is used for light curing, and the exposure curing energy is 850mJ / cm 2 , to obtain a plasma sprayed metal coating.

[0062] Comparative Example 1:

[0063] The difference between the preparation method of the plasma spraying metal coating of Comparative Example 1 and Example 2 lies in the difference in step (1), which is modified as follows: zinc-aluminum alloy is made into zinc-aluminum alloy strip, and then zinc powder, aluminum powder, titanium powder, and cerium oxide powder are mixed with the zinc-aluminum alloy strip according to the mass fraction composition of zinc 75%, aluminum 14.5%, titanium 10%, and cerium ≤ 0.5% to make a spraying alloy powder core wire with a diameter of 2.0 mm. The remaining steps are the same as in Example 2.

[0064] Comparative Example 2:

[0065] The difference between the preparation method of the plasma spraying metal coating of Comparative Example 2 and Example 2 lies in the difference in step (1). Step (1) is modified as follows: zinc powder, aluminum powder, titanium powder, cerium oxide powder, and silicon carbide ceramic powder are mixed to form spraying alloy powder according to the mass fraction components of zinc 42%, aluminum 8%, titanium 5.5%, cerium ≤ 0.5%, and silicon carbide 44%. Step (5) is modified as follows: after the equipment is set according to the plasma spraying process parameters of voltage 132V, current 410A, argon flow rate 145L / min, hydrogen flow rate 11L / min, and spraying distance 115mm, the spraying alloy powder is sprayed on the surface of the substrate with a spraying thickness of 155μm, and then the modified organic coating is scraped on with a scraping thickness of 45μm, and light-cured with an ultraviolet light curing machine with an exposure curing energy of 825mJ / cm 2 The remaining steps are the same as those in Example 2.

[0066] Comparative Example 3:

[0067] The difference between the preparation method of the plasma spraying metal coating of Comparative Example 3 and Example 2 is that step (1) is not performed, and step (5) is modified as follows: after the equipment is set according to the plasma spraying process parameters of voltage 132V, current 410A, argon flow rate 145L / min, hydrogen flow rate 11L / min, and spraying distance 115mm, zinc powder is sprayed on the surface of the substrate with a spraying thickness of 155μm, and then the modified organic coating is scraped on with a scraping thickness of 45μm, and light-cured with an ultraviolet light curing machine, and the exposure curing energy is 825mJ / cm2 The remaining steps are the same as those in Example 2.

[0068] Comparative Example 4:

[0069] The preparation method of the plasma spraying metal coating of Comparative Example 4 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: by weight, 12.23 parts of isophorone diisocyanate, 0.0024 parts of triethylamine, and 22.5 parts of ethyl acetate are mixed uniformly under a nitrogen atmosphere, and 6.73 parts of ethylene glycol dithioacetate are added dropwise at 28°C and 250r / min at a rate of 3 drops per second. After the addition is completed, the mixture is reacted at 28°C and 250r / min for 2.5 hours, and sampling is performed to confirm After the reaction is complete, 5.5 parts of polycarbonate diol and 0.0055 parts of dibutyltin dilaurate are added dropwise at 3 drops per second, and the reaction is carried out at 68° C. and 250 r / min for 3.5 hours. After sampling to confirm that the reaction is complete, 5.72 parts of hydroxyethyl methacrylate and 0.011 parts of p-hydroxyanisole are added dropwise at 3 drops per second, and the reaction is carried out at 68° C. and 250 r / min for 3.5 hours. After sampling to confirm that the reaction is complete, the reaction is stopped, and ethyl acetate is removed by rotary evaporation to obtain modified polythiourethane. The remaining steps are the same as those in Example 2.

[0070] Comparative Example 5:

[0071] The difference between the preparation method of the plasma spraying metal coating of Comparative Example 5 and that of Example 2 lies in the difference in step (3). Step (3) is modified as follows: by mass, in a nitrogen atmosphere, 12.23 parts of isophorone diisocyanate, 0.01 parts of dibutyltin dilaurate, and 22.5 parts of ethyl acetate are mixed uniformly, and 21.5 parts of polycarbonate diol are added dropwise at 28°C and 250r / min at a rate of 3 drops per second. After the addition is completed, the reaction is carried out at 68°C and 250r / min for 3.5 hours. After sampling to confirm that the reaction is complete, 5.72 parts of olefin-modified phosphate and 0.011 parts of p-hydroxyanisole are added dropwise at a rate of 3 drops per second. After the addition is completed, the reaction is carried out at 68°C and 250r / min for 3.5 hours. After sampling to confirm that the reaction is complete, the reaction is stopped, and the ethyl acetate is removed by rotary evaporation to obtain a modified polyurethane. Step (4) is modified as follows: 75 parts of modified polyurethane, 30 parts of diluent, 2.5 parts of photoinitiator and 0.055 parts of catalyst are mixed uniformly in a mixing and defoaming machine to obtain a modified organic coating. The remaining steps are the same as those in Example 2.

[0072] Test Example 1:

[0073] Mechanical properties test: The bonding strength, adhesion and impact strength of the prepared plasma sprayed metal coating are tested to evaluate its mechanical properties. The specific test methods are as follows:

[0074] Bond strength: Refer to GB / T 5210-2006 to test the bond strength of the prepared plasma sprayed metal coating. Five samples are tested in each group and the average value is recorded.

[0075] Adhesion: Refer to GB / T 9286-2021 to test the adhesion of the prepared plasma sprayed metal coating. Test 5 samples in each group and record the lowest level.

[0076] Impact strength: The impact strength of the prepared plasma sprayed metal coating was tested with reference to GB / T 20624.1-2006. The weight of the falling hammer was 1 kg. Five specimens were tested in each group, and the minimum value was recorded.

[0077] The results are shown in Table 1.

[0078] Table 1

[0079] Bond strength / MPa Adhesion Impact strength / cm Example 1 3.04 Level 0 70 Example 2 3.15 Level 0 75 Example 3 3.01 Level 0 70 Comparative Example 1 2.64 Level 0 60 Comparative Example 2 2.85 Level 0 60 Comparative Example 3 2.72 Level 0 60 Comparative Example 4 0.75 Level 4 45 Comparative Example 5 1.44 Level 2 35

[0080] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the plasma spraying metal coating prepared by the present invention has good adhesion and impact resistance.

[0081] By comparing the data in the table, it is shown that the addition of silicon carbide ceramic powder increases the density of the alloy layer, improves the bonding strength, adhesion and impact strength; the effect of making the alloy layer raw material into powder core wire for plasma spraying is better than directly using mixed powder, which has higher density and fewer defects such as microcracks and pores, and effectively improves the bonding strength, adhesion and impact strength; the addition of olefin-modified phosphate ester to organic coatings effectively improves the bonding strength and adhesion, and the phosphate group has good metal chelating properties and can form a phosphating film at the metal-organic interface, which has an excellent effect on improving the bonding strength; the thiol carbamate bond formed by the addition of thiol chain extender in polythiourethane has stronger metal binding properties, and at the same time, the thiol carbamate bond as a dynamic bond has excellent energy absorption capacity, which can effectively improve the impact strength.

[0082] Test Example 2:

[0083] Corrosion resistance test: refer to GB / T 10125-2021 to conduct neutral salt spray test on the prepared salt spray resistant coating. The four sides and the back of the sample are sealed with red glue. The sample is placed at 15-25° to the vertical direction in the salt spray chamber. The test solution is 5wt% sodium chloride solution, and the salt spray settling speed is 80cm 22mL / h on the area, the temperature in the salt spray chamber is 35±2℃, and the pH value of the solution is between 6.5 and 7.2. After 7 days of curing of the plasma spray metal coating, use a utility knife to draw a line parallel to the long side of the test plate on the test plate, and ensure that the line is drawn to the base metal. After edge sealing, the sample is placed in the salt spray test cabinet for salt spray test, and observed every 12 hours. When the unidirectional corrosion of the paint film scratch exceeds 1.5mm, record the salt spray resistance time of the coating. Test 5 samples in each group and record the shortest time.

[0084] The results are shown in Table 2.

[0085] Table 2

[0086] Salt spray resistance time Salt spray resistance time Example 1 1668h Comparative Example 1 1416h Example 2 1692h Comparative Example 2 1548h Example 3 1656h Comparative Example 3 1104h Comparative Example 4 1056h Comparative Example 5 984h

[0087] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the plasma spraying metal coating prepared by the present invention has good corrosion resistance.

[0088] The comparison of the data in the table shows that the addition of silicon carbide powder and the use of powder core wire effectively improve the density of the alloy layer, reduce microcracks and pore defects, reduce the entry path of corrosive media, and improve corrosion resistance; pure zinc coating only has cathodic protection ability, but lacks self-sealing performance, and its corrosion resistance is not as good as that of composite alloys; the addition of olefin-modified phosphate ester also effectively improves the corrosion resistance. The phosphate group has good metal chelating properties, which can form a phosphating film at the metal-organic interface, which can serve as a line of defense to prevent the penetration of corrosive media and improve the corrosion resistance; the addition of thiol chain extender in polythiourethane introduces thioamine with dynamic exchange capacity. The thiocarbamate bonds have the ability of self-repairing, which can fully fill the micro cracks of the alloy coating and further improve the corrosion resistance. The alloy coating formed by the sprayed alloy powder core wire has a self-sealing effect, which can effectively seal the micro cracks of the organic coating upward. The dynamic exchange ability of the thiocarbamate bonds in the organic coating also gives it self-repairing ability, which can repair some smaller cracks. At the same time, the phosphate group also has good metal chelating ability, combined with the complexing ability of nitrogen, sulfur and oxygen elements, it can adsorb metal ions and expand the volume to seal cracks when corrosion occurs. The organic coating and the alloy coating protect each other, and the composed plasma sprayed metal coating has good corrosion resistance.

[0089] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A plasma spraying metal coating, characterized in that: The plasma spraying metal coating is prepared by first spraying the spraying alloy powder core wire on the surface of the substrate by plasma spraying, then scraping the modified organic coating on it by scraping, and then curing it with ultraviolet light; The spray-coated alloy powder core wire is prepared by mixing zinc powder, aluminum powder, titanium powder, cerium oxide powder and silicon carbide ceramic powder with a zinc-aluminum alloy strip through a powder core wire preparation process, wherein the components by mass fraction are 38% to 45% zinc, 7% to 9% aluminum, 5% to 6% titanium, ≤0.5% cerium and 40% to 50% silicon carbide; The modified organic coating is prepared by mixing modified polythiourethane with a diluent, a photoinitiator and a catalyst for defoaming; The modified polythiourethane is prepared by reacting isophorone diisocyanate, ethylene glycol dimercaptoacetate, polycarbonate diol, and olefin-modified phosphate. The olefin-modified phosphate is prepared by reacting monoethyl phosphate with hydroxyethyl methacrylate.

2. A plasma spraying metal coating according to claim 1, characterized in that: The zinc-aluminum alloy strip is made of zinc-aluminum alloy, wherein the aluminum content of the zinc-aluminum alloy is 2wt%, the impurity content is less than 0.01wt%, and the balance is zinc.

3. The plasma spraying metal coating according to claim 1, characterized in that: The diluent is one of dipropylene glycol diacrylate and tripropylene glycol diacrylate.

4. The plasma spraying metal coating according to claim 1, characterized in that: The photoinitiator is one or more of Irgacure 127, Irgacure 184, Irgacure 369, Irgacure 907, and Irgacure 1173.

5. The plasma spraying metal coating according to claim 1, characterized in that: The catalyst is 1,5-diazabicyclo[4.3.0]non-5-ene.

6. The plasma spraying metal coating according to claim 1, characterized in that: The model of the polycarbonate diol is P997425, and the weight average molecular weight is 500.

7. A method for preparing a plasma sprayed metal coating, characterized in that: The method comprises the following preparation steps: (1) The zinc-aluminum alloy is made into a zinc-aluminum alloy strip, and then zinc powder, aluminum powder, titanium powder, cerium oxide powder, and silicon carbide ceramic powder are mixed according to the mass fraction composition of zinc 38% to 45%, aluminum 7% to 9%, titanium 5% to 6%, cerium ≤ 0.5%, and silicon carbide 40% to 50%, and the mixture is mixed with the zinc-aluminum alloy strip to form a melt-sprayed alloy powder core wire with a diameter of 2.0 mm; (2) at 40-45° C., monoethyl phosphate and hydroxyethyl methacrylate were uniformly mixed in a molar ratio of 1:1, and then stirred in a closed environment at 80-85° C. and 200-300 r / min for 4-5 hours, and then cooled and purified to obtain olefin-modified phosphate; (3) According to the mass fraction, 11.11-13.34 parts of isophorone diisocyanate, 0.0022-0.0027 parts of triethylamine and 20-25 parts of ethyl acetate were mixed uniformly under nitrogen atmosphere, and 5.26-7.99 parts of ethylene glycol dimercaptoacetate were added dropwise at 25-30°C and 200-300 r / min at a rate of 2-3 drops per second. After the addition was completed, the mixture was reacted at 25-30°C and 200-300 r / min for 2-3 hours. After sampling to confirm that the reaction was complete, 5-6 parts of polycarbonate were added dropwise at a rate of 2-3 drops per second. Acid ester diol, 0.005-0.006 parts of dibutyltin dilaurate, after the addition is completed, react at 65-70°C, 200-300r / min for 3-4h, take samples to confirm that the reaction is complete, then add 4.76-7.15 parts of olefin modified phosphate ester and 0.01-0.012 parts of p-hydroxyanisole at a rate of 2-3 drops per second, after the addition is completed, react at 65-70°C, 200-300r / min for 3-4h, take samples to confirm that the reaction is complete, stop the reaction, remove ethyl acetate by rotary evaporation, and obtain modified polythiourethane; (4) Mixing 70 to 80 parts by mass of modified polythiourethane, 25 to 35 parts of diluent, 2 to 3 parts of photoinitiator, and 0.05 to 0.06 parts of catalyst in a mixing and defoaming machine to obtain a modified organic coating; (5) After setting the equipment according to the plasma spraying process parameters, the sprayed alloy powder core wire is sprayed on the surface of the substrate with a spraying thickness of 150-160 μm, and then the modified organic coating is scraped on with a scraping thickness of 40-50 μm. The UV light curing machine is used for light curing, and the exposure curing energy is 800-850 mJ / cm 2 , to obtain a plasma sprayed metal coating.

8. The method for preparing a plasma spraying metal coating according to claim 7, characterized in that: The particle sizes of the zinc powder, aluminum powder, titanium powder, cerium oxide powder and silicon carbide ceramic powder in step (1) are all 325 meshes.

9. The method for preparing a plasma spraying metal coating according to claim 7, characterized in that: The plasma spraying process parameters of step (5) are as follows: voltage 130-135 V, current 400-420 A, argon flow rate 140-150 L / min, hydrogen flow rate 10-12 L / min, and spraying distance 110-120 mm.

10. The method for preparing a plasma spraying metal coating according to claim 7, characterized in that: In step (5), the substrate may be made of any metal material and may be pre-treated by grinding, cleaning and then sandblasting the substrate.